Achieving a Green Solution: Limitations and Focus Points for Sustainable Algal Fuels - Blanca Antizar-Ladislao; Douglas Aitken (Energies, 2012)
Research investigating the potential of producing biofuels from algae has been enjoying a recent revival due to heightened oil prices, uncertain fossil fuel sources and legislative targets aimed at reducing our contribution to climate change. If the concept is to become a reality however, many obstacles need to be overcome. Recent studies have suggested that open ponds provide the most sustainable means of cultivation infrastructure due to their low energy inputs compared to more energy intensive photobioreactors. Most studies have focused on strains of algae which are capable of yielding high oil concentrations combined with high productivity. Yet it is very difficult to cultivate such strains in open ponds as a result of microbial competition and limited radiation-use efficiency. To improve viability, the use of wastewater has been considered by many researchers as a potential source of nutrients with the added benefit of tertiary water treatment however productivity rates are affected and optimal conditions can be difficult to maintain year round. This paper investigates the process streams which are likely to provide the most viable methods of energy recovery from cultivating and processing algal biomass. The key findings are the importance of a flexible approach which depends upon location of the cultivation ponds and the industry targeted. Additionally this study recommends moving towards technologies producing higher energy recoveries such as pyrolysis or anaerobic digestion as opposed to other studies which focused upon biodiesel production.